2018
DOI: 10.12671/jkfs.2018.31.3.79
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Extramedullary Reduction in Unstable Intertrochanteric Fracture: A Biomechanical Study Using Cadaver Bone

Abstract: To prevent excessive sliding and subsequent fixation failures in unstable intertrochanteric fractures with posteromedial comminution, extramedullary reduction through overlapping of the anteromedial cortices of both proximal and distal fragments as a buttress has been introduced. The purpose of this study was to compare the biomechanical properties between two reduction methodsintramedullary reduction and extramedullary reduction-in treating unstable intertrochanteric fractures with posteromedial comminution (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…However, blade sliding was not blocked by cortical apposition in the intramedullary reduction group, and after that, cut-out occurred following varus malposition and rotation of proximal fragment. A previous biomechanical study demonstrated results similar to those in the extamedullary reduction group which had better resistance against axial loading compared with the intramedullary reduction group 17) .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, blade sliding was not blocked by cortical apposition in the intramedullary reduction group, and after that, cut-out occurred following varus malposition and rotation of proximal fragment. A previous biomechanical study demonstrated results similar to those in the extamedullary reduction group which had better resistance against axial loading compared with the intramedullary reduction group 17) .…”
Section: Discussionsupporting
confidence: 55%
“…For the prevention of mechanical complications, appropriate fracture reduction and blade position are essential 15 16) . Anatomical reduction or extramedullary reduction with medial cortical overlap known as the Wayne-County technique are associated with biomechanical stability compared with intramedullary reduction 17) . Intramedullary reduction in comminuted intertrochanteric fractures without posteromedial cortical support is prone to excessive sliding and varus malposition of proximal fragment leading to mechanical failures.…”
Section: Introductionmentioning
confidence: 99%
“…The authors believed that the Chang's criteria which emphasized anteromedial cortical contact was more reliable and effective than the Baumgaertner's criteria in predicting postoperative mechanical complications and worthy of clinical applications. Biomechanical [14] and clinical [15] researches have confirmed that the anteromedial cortical contact can not only share stress load from the internal fixation device (mechanical role), but also can promote close contact and fracture healing at the fracture sites (biological role), both of which are benefit for maintaining the normal femoral neck length and the neck-shaft angle.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of EM reduction have been recently reported in several clinical and biomechanical studies 1 2 4 5) . Additionally, several reduction techniques were noted to remove the head-neck fragment from the intramedullary (IM) space of the distal femoral shaft fragment 2 4 6) to achieve fracture reduction in the EM position.…”
Section: Introductionmentioning
confidence: 91%
“…One of the major reasons for treatment failure in pertrochanteric hip fracture surgeries is excessive sliding of the lag screw 1) . Extramedullary (EM) reduction, defined as the medial cortex of the head-neck fragment located outside of the medullary canal of the distal shaft fragment, has been introduced to prevent excessive postoperative sliding or failure of the lag screw in pertrochanteric fracture surgeries 1 2 3 4 5) . In EM reduction, the anteromedial cortical bone of the proximal fragment has bony contact with the distal fragment during sliding and theoretically plays the role of a buttress from the beginning, preventing excessive sliding and varus deformity of the proximal fragment 5) .…”
Section: Introductionmentioning
confidence: 99%